l-Glutamic acid induced the colonization of high-efficiency nitrogen-fixing strain Ac63 (Azotobacter chroococcum) in roots of Amaranthus tricolor - Wang, Yi-Fan; Wang, Jun-Feng; Xu, Zhi-Min; She, Shao-Hua; Yang, Jun-Qing; Li, Qu-Sheng (Plant and soil, 2020)
Aims The aim of this study was to evaluate its feasibility of a non-symbiotic nitrogen-fixing strain, Ac63 ( Azotobacter chroococcum ), to promote biomass of common vegetable crops and its colonization mechanisms in their roots. Methods Root exudates of common vegetables, including Amaranthus tricolor (AT), Willow amaranth (WA), Chrysanthemum coronarium (CC), cabbage, and lettuce, were collected, and a chemotaxis assay with Ac63 was performed. Components in exudates for the most differential chemotaxis effect crops (AT and lettuce) were determined with GC-MS. Then, the traditional screening strategies of chemotaxis, swarming, and in vitro were utilized to find the signal molecule for this strain. Finally, the colonization effects of Ac63 in roots of these two crops were verified with a soil pot experiment. Results Chemotaxis effects of root exudates on Ac63 follow the lists of AT > WA > CC > cabbage ≈ control (water) ≈ lettuce. With a 30-μM concentration of l -glutamic acid, bacterial amount of Ac63 in chemotaxis and in vitro was observed with 2.9- and 7.4-times enhancement compared with that in the control. Laser confocal microscopy indicated that l -glutamic acid induced Ac63 to form a robust biofilm in roots, suggesting that l -glutamic acid is a signal molecule for the colonization of this strain. Soil pot assay showed that the biomass, chlorophyll, and available nitrogen of AT significantly increased than those of lettuce after Ac63 inoculation, resulting from this strain was substantially increased in roots of AT with l -glutamic acid secretion. Conclusion l -Glutamic acid induced the colonization of high-efficiency nitrogen-fixing strain Ac63 in AT roots, which provides a practical information for its agricultural applications.